Rain conditions affect the transmission of Streaming video data on Aeromodelling - Agus Suhendar; Murti Retnowo (Institut Teknologi Dirgantara Adisutjipto, 2023)
Streaming is the process of sending data continuously that can be broadcast over the internet. FPV (First-person view) is a method used to control radio control vehicles from the pilot. Analysis of live video streaming service on FPV aeromodelling with standard configurations to determine the maximum results for live video streaming service on FPV aeromodelling. Distance measurements and environmental conditions are also necessary to determine the performance of live video streaming. Then, the performed on a Quality of Service (QoS) analysis, including measurement of delay, jitter, and throughput using Wireshark. From the tests that have been carried out, the comparison of the best value between the measurement of data delay with a value of 0.0085 m/s, for a jitter of 20.294 m/s and a throughput of 0.009 m/s is obtained, all of which are in accordance with the standards recommended by ITU-T. So that, the overall QoS obtained gives sufficient results.